'Sea law phalanx' initiative in China. Issue 1 (2nd January 2018) - Chu, Bei-Ping; Chang, Yen-Chiang
ABSTRACT: The 'Sea Law Phalanx' Initiative has recently been lunched under the auspicious of the China Law Society. Its main task is to gather legal scholars who specialise in the area of maritime law and the law of the sea to work together toward one aim. In addition, establishing the concept of sea law in China would help to integrate the current fragmentation of marine-related legal regulations. This would encourage achieving the target of systematisation and improvement of the law, through the concept of sea law, thus achieving a dynamic balance, characterised by up-and-down order and internal-and-external coordination. In doing so, this will not only act as an active participant in the unification of international marine related legislation but also help to construct the, 'One Belt and One Road', initiative in China.